Restauração de imagens de microscopia confocal utilizando técnicas POCS - Stelzer, Murilo (2005)
Computer Optical Sectioning Microscopy (COSM) is widely used in morphological studies of cellular structures. COSM appears as a great challenge to digital image processing, because the large size of the three-dimensional files. The major problem in COSM is the blurring, which practically turn the image unusable without the use of digital image processing techniques. In this work, based on projection onto convex set were developed image processing techniques to restore COSM images, obtained by a confocal microscope. Although confocal microscope presents less blurring than the wide field microscope, it has a larger Poisson noise level. To reduce the Poisson noise the Anscombe Transform (AT) was used as well a pointwise Wiener Filter. The POCS methods were evaluated by means of simulations, using synthetic images (phantom), and the results was evaluated by ISNR (Improvement in Signal Noise Ratio) and UIQ (Universal Quality Index). The developed algorithms, using RAP (Row Action Projection) present satisfactory results, but the computational costs were expensive.